Development of fatigue cracks from mechanically machined scratches on 2024-T351 aluminium alloy - Part II: finite element analysis and prediction method - Cini, Andrea; Irving, Phil E. (Wiley, 2016)
A prediction method to evaluate the effect of scratch geometry on fatigue life of aluminium structures containing scribe marks was developed on the basis of the experimental results described in Part I of this paper. Finite element calculations were performed on scribed samples to investigate the local stress around scribes. Elastic and elastic plastic stress and strain distributions at the scribe root were computed under monotonic and cyclic tensile and bending loads evaluating the driving force behind initiation and propagation from scribes. Scribe shape, size and cladding regulated stress and strain distributions in the neighbourhood of scribe roots. Fatigue life of tested scribed samples was divided into initiation life, defined as the cycles spent to develop a 50 μm deep crack at scribe roots, and the remaining propagation life up to failure. Striation counting measurements were used to calculate propagation lives by integrating linear elastic da/dN vs. ΔK curves. Only up to a maximum of 38% of total fatigue life was spent to propagate an initial 50 μm deep crack from scribe roots. The theory of critical distances was successfully applied to predict initiation lives of scribed samples from elastic stress distributions. A plastic correction was also suggested in the frame of the theory of critical distances, to correlate initiation lives of clad and unclad specimens
Keywords: Notch fatigue; scratches; scribe marks; small cracks; notch stress; theory of critical distances